Peran Kemampuan Pengguna Teknologi Informasi Menuju Transformasi Sumberdaya Manusia di Era Revolusi Industri 4.0 - Ari Muhardono; Chalimah Chalimah; Mahardika Diazwara; Mar'ah Mar'ah (President University, 2022)
Human resources (HR) transformation is strongly guided in the industrial revolution 4.0 Era. The ability of users of information technology has an important role in the HR transformation. Therefore, this study aims to examine the effect of the application of information technology on the HR transformation with user capabilities as a moderating variable in the Savings and Loans Cooperative and Syari'ah Baitut Tamwil Muhammadiyah (KSPPS BTM) Central Java. Data collection was carried out by distributing questionnaires to the all managers of KSPPS BTM in the Central Java region. Data analysis using simple linear regression. To test for the first hypothesis and the second hypothesis using the MRA (Moderated Regression Analysis) method. The results show that the application of information technology has a positive and significant effect on HR transformation, while the moderating variable from the results of the second hypothesis test shows that the user ability variable has a positive and insignificant effect on the relationship between the application of information technology and HR transformation, but the user ability variable weakens the interaction between the variables of the application of information technology to the HR transformation. So it can be said that the user's ability is a potential moderating variable (Homologiser). Keywords: Application of Information Technology, User Capabilities, HR Transformation, Moderating Variables